Excess intraoperative fluid volume administration is associated with pancreatic fistula after pancreaticoduodenectomy: A retrospective multicenter study - Han, In Woong (Medicine (Baltimore), 2017)
Recent studies on perioperative fluid administration in patients undergoing pancreaticoduodenectomy (PD) have suggested that increased fluid loads are associated with worse perioperative outcomes. The purpose of this study was to investigate the relationship between intraoperative fluid (IOF) administration and postoperative pancreatic fistula (POPF), and to determine additional risk factors affecting pancreatic fistula in patients undergoing PD. From 2005 to 2014, a total of 182 patients with various periampullary diseases after PD were reviewed retrospectively at Dongguk University Ilsan Hospital, Chung-Ang University Hospital, and Dongnam Institute of Radiological and Medical Sciences. Patients were assigned to high or low IOF groups based on more or less fluid administration for supplementation of estimated blood loss and maintenance volume (12.5 mL/kg/h) than planned, respectively. The associations between IOF administration, pancreatic fistula development, and perioperative outcomes were evaluated. A total of 98 patients were assigned to the high-IOF group, and 84 to the low-IOF group. Risk factors for pancreatic fistula after univariate analysis were assignment to the high-IOF group, higher preoperative serum hemoglobin level, ampullary or bile duct cancer, pylorus preserving PD, small pancreatic duct, duct-to-mucosa pancreatojejunostomy, use of a stent, and mesh application to pancreatojejunal anastomosis. Among these, assignment to the high-IOF group (hazard ratio [HR] = 5.501, 95% CI 1.624–18.632, P = .006) and a small (<4 mm) pancreatic duct (HR = 4.129, 95% CI 1.569–14.658, P = .035) were identified as independent risk factors for the development of pancreatic fistula after multivariate analysis. However, long-term survival rate did not differ according to IOF group or duct size. Excessive IOF volume administration is associated with an increased incidence of pancreatic fistula after pancreaticoduodenectomy.